2022
DOI: 10.1371/journal.pone.0269002
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of atherosclerotic cardiovascular diseases before statin therapy initiation: Knowledge, attitude, and practice of physicians in Yemen

Abstract: Background Risk evaluation of atherosclerotic cardiovascular disease (ASCVD) remains the cornerstone of primary prevention. The cardiovascular risk assessment can guide the decision-making on various preventive measures such as initiating or deferring statin therapy. Thus, our study aimed to assess the physicians’ knowledge, attitude, and practices regarding atherosclerotic cardiovascular diseases risk assessment. Also, we evaluated the physician-patient discussion and counseling practices before statin therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Despite the availability of ASCVD risk calculators, barriers to their implementation include time constraints, accessibility limitations, poor clinician uptake, patient fears, lack of documented workflows, staffing issues, concerns about out-of-pocket costs, and inadequate communication within the team [40] . In Yemen, a low-income country in West Asia, there was a highly positive attitude toward ASCVD risk assessment however, overall knowledge was low, and practices were suboptimal [41] . Persons with longer years in practice, specialization in cardiology, and compliance with specific guidelines were most associated with higher knowledge and better practices.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the availability of ASCVD risk calculators, barriers to their implementation include time constraints, accessibility limitations, poor clinician uptake, patient fears, lack of documented workflows, staffing issues, concerns about out-of-pocket costs, and inadequate communication within the team [40] . In Yemen, a low-income country in West Asia, there was a highly positive attitude toward ASCVD risk assessment however, overall knowledge was low, and practices were suboptimal [41] . Persons with longer years in practice, specialization in cardiology, and compliance with specific guidelines were most associated with higher knowledge and better practices.…”
Section: Discussionmentioning
confidence: 99%
“…This knowledge gap among healthcare providers could result in the underutilization of statins among patients with clinical indications. Indeed, we recently have reported knowledge and practice gaps regarding CVD risk assessment among physicians and pharmacists [12,13].…”
Section: Clinical Knowledge About Statin Therapymentioning
confidence: 99%
“…However, healthcare providers' lack of knowledge about up-to-date guideline recommendations is one of the most common barriers to guideline implementation in clinical practice [9]. Previous studies have reported knowledge gaps among physicians and/or pharmacists regarding cholesterol management guidelines and/or CVD risk assessment before statin therapy initiation [10][11][12][13]. For example, two studies from the USA that were done among healthcare providers [14] and clinical pharmacists [15] reported several knowledge gaps about guidelines, particularly those related to ASCVD risk assessment and statin therapy clinical indications.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular diseases (CVDs) happen due to malfunctions in the heart as well as blood vessels. CVDs are one of the main causes of global deaths as issued by the World Health Organization (WHO) [1], CVDs share 32% of the global death causes in 2019. ECG is an essential tool for CVDs diagnoses and treatment, also it is required for continuous heart monitoring.…”
Section: Introductionmentioning
confidence: 99%